Importance of carpenter bee, xylocopa varipuncta (Hymenoptera: Apidae) as pollination agent for mangrove community of setiu Wetlands, Terengganu, Malaysia - Wahizatul Afzan Azmi,; Roziah Ghazi,; Nor Zalipah Mohamed, (Universiti Kebangsaan Malaysia, 2012)
A study on the importance of Xylocopa varipuncta (Hymenoptera: Apidae) as pollination agent was conducted at the Setiu Mangrove Forest, Terengganu from September to December 2010. The objective of this study was to identify the pollens collected by carpenter bees (X. varipuncta) in the mangrove community of Setiu Wetlands. A total of 35 types of pollens were collected from the body of X. varipuncta and only 10 types of the pollens were successfully identified. The identified pollens were of Avicennia alba, Lumnitzera racemosa, Sonneratia caseolaris, S. ovata and Rhizophora apiculata from exclusive mangroves, while Suregada multiflora, Melaleuca cajuputi, Derris trifoliata, Acacia auriculiformis and Hibiscus tiliaceus were from non-exclusive mangroves. Melaleuca cajuputi was the highest number of pollen carried by X. varipuncta. This study showed that X. varipuncta is an important pollen carrier in the mangrove community of Setiu Wetlands, Terengganu.